Ambulatory blood pressure changes after renal sympathetic denervation in patients with resistant hypertension - Mahfoud, Felix; Ukena, Christian; Schmieder, Roland E.; Cremers, Bodo; Rump, Lars C.; Vonend, Oliver; Weil, Joachim; Schmidt, Martin; Hoppe, Uta C.; Zeller, Thomas; Bauer, Axel; Ott, Christian; et al. (Circulation, 2013)
Background—Catheter-based renal sympathetic denervation (RDN) reduces office blood pressure (BP) in patients with resistant hypertension according to office BP. Less is known about the effect of RDN on 24-hour BP measured by ambulatory BP monitoring and correlates of response in individuals with true or pseudoresistant hypertension.Methods and Results—A total of 346 uncontrolled hypertensive patients, separated according to daytime ambulatory BP monitoring into 303 with true resistant (office systolic BP [SBP] 172.2±22 mm Hg; 24-hour SBP 154±16.2 mm Hg) and 43 with pseudoresistant hypertension (office SBP 161.2±20.3 mm Hg; 24-hour SBP 121.1±19.6 mm Hg), from 10 centers were studied. At 3, 6, and 12 months follow-up, office SBP was reduced by 21.5/23.7/27.3 mm Hg, office diastolic BP by 8.9/9.5/11.7 mm Hg, and pulse pressure by 13.4/14.2/14.9 mm Hg (n=245/236/90; P for all <0.001), respectively. In patients with true treatment resistance there was a significant reduction with RDN in 24-hour SBP (−10.1/−10.2/−11.7 mm Hg, P<0.001), diastolic BP (−4.8/−4.9/−7.4 mm Hg, P<0.001), maximum SBP (−11.7/−10.0/−6.1 mm Hg, P<0.001) and minimum SBP (−6.0/−9.4/−13.1 mm Hg, P<0.001) at 3, 6, and 12 months, respectively. There was no effect on ambulatory BP monitoring in pseudoresistant patients, whereas office BP was reduced to a similar extent. RDN was equally effective in reducing BP in different subgroups of patients. Office SBP at baseline was the only independent correlate of BP response.Conclusions—RDN reduced office BP and improved relevant aspects of ambulatory BP monitoring, commonly linked to high cardiovascular risk, in patients with true-treatment resistant hypertension, whereas it only affected office BP in pseudoresistant hypertension.Clinical Trial Registration—URL: http://www.clinicaltrials.gov. Unique identifiers: NCT00664638 and NCT00888433.
Gesehen am 11.06.2021